Formation features of medical services market in Ukraine at the present stage - Гапонова, Еліна (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
The author analyzes the existing problems of social marketing at the medical care market, considering the total market approach. The article studies the effectiveness of care services monitoring, cooperation of public-private sector of medicine and qualitative control of medical services. The author pays attention is given to the concepts such as market size of medical services, their availability and market prices, sustainable development of the health care.